Kontribusi Penguatan Guru Mata Pelajaran dan Kepercayaan Diri Siswa terhadap Keaktifan Siswa dalam Belajar - Zamratul Aini; Herman Nirwana; Marjohan Marjohan (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2018)
The purpose of this reaserch is to describe: (1) reinforcement teacher subjects accepted students, (2) the confidence of students, (3) the activeness of students in learning, , and (4) contribution the reinforcement subjects teachers and confidence individually or together to the activeness of students in learning. This research used quantitative approach and correlation method. The population of this reaserch were 619 students of SMA Pertiwi 1 Padang in the class X and XI. The sampel were 243 students than were chosen by using propotional stratafied random sampling. The instruments used Scale of Activeness Students in Learning with reliability 0,922, the Scale of Reinforcement Teacher with reliability 0,865, and Scale of Self Confidence with reliability 0,915  Likert model. Research data were analyzed using simple regression and regression. The results of this research show that on average: (1) the level of reinforcement teacher subjects were on the category either, (2) the level of the students’s confidence are in the category of middle, (3) the level of activeness students are on a high category, (4) reinforcement teacher subjects contribute significantly to the activeness of the students in learning of 15.6%, confidence contributes significantly to the activenes of the students in learning of 17,9%, and reinforcement teachers subjects and confidence collectively contribute significantly the activiveness student in learning of 25,4%. The implications of the research can be used as input to steer  counsellors in providing guidance and counselling services.